Self-reported drunkenness among adolescents in four sub-Saharan African countries: associations with adverse childhood experiences - Crichton Joanna; Beguy Donatien; Kabiru Caroline W; Ezeh Alex C (BMC, 2010)
Abstract Background Consumption of alcohol is associated with acute and chronic adverse health outcomes. There is a paucity of studies that explore the determinants of alcohol use among adolescents in sub-Saharan Africa and, in particular, that examine the effects of adverse childhood experiences on alcohol use. Methods The paper draws on nationally-representative data from 9,819 adolescents aged 12-19 years from Burkina Faso, Ghana, Malawi, and Uganda. Logistic regression models were employed to identify correlates of self-reported past-year drunkenness. Exposure to four adverse childhood experiences comprised the primary independent variables: living in a food-insecure household, living with a problem drinker, having been physically abused, and having been coerced into having sex. We controlled for age, religiosity, current schooling status, the household head's sex, living arrangements, place of residence, marital status, and country of survey. All analyses were conducted separately for males and females. Results At the bivariate level, all independent variables (except for coerced sex among males) were associated with the outcome variable. Overall, 9% of adolescents reported that they had been drunk in the 12 months preceding the survey. In general, respondents who had experienced an adverse event during childhood were more likely to report drunkenness. In the multivariate analysis, only two adverse childhood events emerged as significant predictors of self-reported past-year drunkenness among males: living in a household with a problem drinker before age 10, and being physically abused before age 10. For females, exposure to family-alcoholism, experience of physical abuse, and coerced sex increased the likelihood of reporting drunkenness in the last 12 months. The association between adverse events and reported drunkenness was more pronounced for females. For both males and females there was a graded relationship between the number of adverse events experienced and the proportion reporting drunkenness. Conclusions We find an association between experience of adverse childhood events and drunkenness among adolescents in four sub-Saharan African countries. The complex impacts of adverse childhood experiences on young people's development and behavior may have an important bearing on the effectiveness of interventions geared at reducing alcohol dependence among the youth.